Studi Morfometrik Daun Macaranga Thou. di Hutan Pendidikan dan Penelitian Biologi (HPPB) - Agung Putra Utama; - Syamsuardi; Ardinis Arbain (Jurnal Biologi Universitas Andalas, 2012)
The morphometric study of Macaranga Thou. (Euphorbiaceae) leaf was carried out from February to June 2012 at The Biological Education and Research Forest (HPPB), Herbarium ANDA and Plant Taxonomy Laboratory of Biology Department, Faculty of Mathematics and Natural Sciences Andalas University, Padang. The survey method was used in this research, the observation and direct collection were performed in the field. The samples were identified based on vegetative characters. The data of the leaf measurements were analyzed by PAST ver. 2.10 programs. It was found six species of Macaranga (M. depressa, M. gigantea, M. hypoleuca, M. javanica, M. tanarius, and M. triloba) and there were identified differentian of characters for each species of Macaranga. The lobes, margo, ratio and types of leaf nervatio used to differentiation. Identification keys based on leaf character could be used to identify Macaranga species. Numerically, species in Macaranga genus could be classified.Keywords: character, Macaranga, morphometric, leaf, HPPB